Alternatives to allogeneic platelet transfusion. (21st September 2016) - Desborough, Michael J. R.; Smethurst, Peter A.; Estcourt, Lise J.; Stanworth, Simon J.
Summary: Allogeneic platelet transfusions are widely used for the prevention and treatment of bleeding in thrombocytopenia. Recent evidence suggests platelet transfusions have limited efficacy and are associated with uncertain immunomodulatory risks and concerns about viral or bacterial transmission. Alternatives to transfusion are a well‐recognised tenet of Patient Blood Management, but there has been less focus on different strategies to reduce bleeding risk by comparison to platelet transfusion. Direct alternatives to platelet transfusion include agents to stimulate endogenous platelet production (thrombopoietin mimetics), optimising platelet adhesion to endothelium by treating anaemia or increasing von Willebrand factor levels (desmopressin), increasing formation of cross‐linked fibrinogen (activated recombinant factor VII, fibrinogen concentrate or recombinant factor XIII), decreasing fibrinolysis (tranexamic acid or epsilon aminocaproic acid) or using artificial or modified platelets (cryopreserved platelets, lyophilised platelets, haemostatic particles, liposomes, engineered nanoparticles or infusible platelet membranes). The evidence base to support the use of these alternatives is variable, but an area of active research. Much of the current randomised controlled trial focus is on evaluation of the use of thrombopoietin mimetics and anti‐fibrinolytics. It is also recognised that one alternative strategy to platelet transfusion is choosing not to transfuse at all.